PREVALENSI INFEKSI SOIL TRANSMITTED HELMINTH PADA PENGRAJIN GENTENG DI DESA WIRUN MOJOLABAN SUKOHARJO MENGGUNAKAN METODE DIRECT DAN INDIRECT - Fitria Diniah Janah Sayekti; Muhammad Taufiq Qurrohman; Dwi Haryami (Jurusan Teknologi Laboratorium Medis, Poltekkes Kemenkes Denpasar, 2023)
Background : Soil Transmitted Helminths (STH) is an intestinal nematode which in its life cycle requires soil for the egg maturation process. Included in this group are Ascaris lumbricoides, Trichuris trichiura, and Hookworm. Lack of attention to clean living behavior can make a person easily infected with helminthiasis. One profession that is closely related to STH infection is work related to soil, including tile craftsmen.Wirun Village in Mojolaban District, Sukoharjo Regency has residents who partly work as roof tile craftsmen. In carrying out their profession, tile craftsmen sometimes do not use personal protective equipment such as gloves and footwear so that they are in direct contact with the ground and have a potential risk of STH infection. Aims:This study aims to determine the prevalence of Soil Transmitted Helminths (STH) using two methods, direct and indirect.Methode :The direct method is carried out to see the presence of eggs or STH larvae with a faster time. The indirect method is carried out by adding special ingredients that can catch worm eggs or larvae. The indirect technique used in this study was to use saturated NaCl flotation. The results:Based on the research results, it can be seen that 6.67% of the respondents were positively infected with STH using either direct or indirect methods. The STH species found was Ascaris lumbricoides. Based on this, it can be seen that the use of the 2 methods does not affect the different results. Conclusion : The prevalence of soil-transmitted helminth infection among tile craftsmen in Wirun village is low because only 6.67% of respondents were found to be positively infected